2000
DOI: 10.1159/000016094
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing Disorders following Acute Stroke: Prevalence and Diagnostic Accuracy

Abstract: We prospectively examined 128 patients with acute first-ever stroke to determine the prevalence of swallowing disorders, the diagnostic accuracy of our clinical assessment of swallowing function compared with videofluoroscopy, and interobserver agreement for the clinical and videofluoroscopic diagnosis of swallowing disorders and aspiration. We found clinical and videofluoroscopic evidence of a swallowing disorder in 51% [95% confidence interval (CI) 42–60%] and 64% (95% CI 55–72%) of patients, respectively, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
215
2
14

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(247 citation statements)
references
References 27 publications
10
215
2
14
Order By: Relevance
“…The prevalence of oropharyngeal dysphagia in patients with stroke reported in the literature varies widely from 23% to 91% (3,5,15,22,23,27,29,34,45) . This variation may be explained by the methods applied in the various studies, by the different severity and by the difference in the time of evaluation of patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of oropharyngeal dysphagia in patients with stroke reported in the literature varies widely from 23% to 91% (3,5,15,22,23,27,29,34,45) . This variation may be explained by the methods applied in the various studies, by the different severity and by the difference in the time of evaluation of patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Using a combination of videofluoroscopy and bedside swallowing examination, Mann, Hankey & Cameron (2000) reported that aspiration was present in 49% of a cohort of 128 acute stroke patients. By six months post stroke, 97 of 112 survivors had returned to their pre-stroke diet (Mann, Hankey & Cameron, 1999).…”
Section: Studies Of Dysphagia In Acute Stroke Patientsmentioning
confidence: 99%
“…Stroke has been reported to be associated with dysphagia, the incidence of which range from 23 to 50 % [16][17][18][19][20][21][22][23][24]. Increased risk of aspiration pneumonia, dehydration and malnutrition have been reported in stroke patients as a consequence of dysphagia [25][26][27][28].12 of our patients had middle cerebral artery infarct showing the symptoms of aphasia(4 with Brocas aphasia and 8 with global aphasia).Eight of them had severe dysphagia and two of them had moderate dysphagia.…”
Section: Resultsmentioning
confidence: 99%